Tagalis graziae, a new species of Saicinae from the Chocó biogeographic region in Colombia (Hemiptera: Reduviidae) - Castro-Huertas, Valentina; Forero, Dimitri (Zootaxa, 2021)
Tagalis graziae sp. nov., is described from a specimen collected in Risaralda, Colombia, in an area considered part of the Chocó biogeographic region. Among the species of Tagalis with a large and nearly horizontal posteromedial process of the pygophore, T. graziae sp. nov. can be recognized by its coloration pattern, in particular by having the profemur with a basal and apical dark brown band, the apex of the meso and metafemur with an apical narrow dark brown band, and the supracoxal lobes dark brown. Digital images of external morphological characters and of the genitalia are provided. An updated key to the species of Tagalis is presented to facilitate the identification of the new species.